Implementing ERISA: Of Policies and “Plans” - Peter J. Wiedenbeck (Washington University Law Quarterly, 1994)
There have been dramatic changes in the benefits field since the passage of the Employee Retirement Income Security Act of 1974 (ERISA). Most notably, employers' cutbacks in health insurance coverage and cost shifting in response to escalating medical care costs have spawned the current national debate over health care reform.19 Less visible, but similarly consequential, is the proliferation of special statutory exclusions from gross income for a variety of fringe benefits.
Keywords: Employee benefits; Qualified benefit plans; Retirement benefits; Employee Retirement Income Security Act of 1974; United States; Employee fringe benefits